2023
DOI: 10.1039/d2ee03342a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nucleation and crystallization in PbI2 films promoting preferential perovskite orientation growth for efficient solar cells

Abstract: Formamidinium (FA)-rich lead iodide perovskite solar cells (PSCs) are gaining popularity because of their excellent photovoltaic performance. Nevertheless, the FA-rich perovskites processed by a two-step sequential deposition method usually possess...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
62
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 58 publications
4
62
0
Order By: Relevance
“…7,8 Residual or excess PbI 2 has been widely employed for high-performance PSCs manufactured using both one-step 9 and two-step 10 procedures since it has been shown that even a small amount of excess PbI 2 can improve photovoltaic performance due to its passivation effect. [11][12][13][14][15][16][17][18] However, the long-term stability of PSCs is compromised by the fact that excess PbI 2 readily decomposes under light illumination into metallic lead (Pb 0 ) and iodine (I 2 ). [19][20][21] Particularly, characterization using thermo-and light-coupled quadrupole mass spectrometry has demonstrated the photodecomposition of PbI 2 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Residual or excess PbI 2 has been widely employed for high-performance PSCs manufactured using both one-step 9 and two-step 10 procedures since it has been shown that even a small amount of excess PbI 2 can improve photovoltaic performance due to its passivation effect. [11][12][13][14][15][16][17][18] However, the long-term stability of PSCs is compromised by the fact that excess PbI 2 readily decomposes under light illumination into metallic lead (Pb 0 ) and iodine (I 2 ). [19][20][21] Particularly, characterization using thermo-and light-coupled quadrupole mass spectrometry has demonstrated the photodecomposition of PbI 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] Solution‐processed deposition presents a facile, controllable, and versatile technique to fabricate high‐quality perovskite films, which are widely used and generate high‐performance PSC devices. [ 6–9 ] As an alternative technique, vapor‐based deposition provides a uniform and dense perovskite (PVSK) film, with less influence from solvents and easy integration with commercial thin film photovoltaic manufacturing. [ 10–14 ] Vapor‐based deposition methods commonly include co‐evaporation deposition, [ 10,15,16 ] sequential vapor deposition, [ 17–21 ] and hybrid chemical vapor deposition (HCVD).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that the long-term vacuum treatment in HCVD can damage the electron transport layer (ETL) in PSCs with the n-i-p structure, which not only reduces the carrier transport but also increases the defect density at the ETL/PVSK interface, leading to a poor efficiency. [28][29][30] Some additional buffer layers such as C 60 , [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), triphenylphosphine oxide (TPPO), and K 2 SO 4 have been shown to protect the ETL (i.e., SnO 2 and TiO 2 ). [28,29,31,32] However, the efficiency of the resultant devices still lags behind the solution process.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, extensive research has been done to better understand its fundamentals and power conversion efficiency (PCE). However, compared with Cu(In,Ga) Se 2 (CIGS), [4,5] GaAs, [6] CdTe, [7] and perovskite [8,9] solar cells whose PCE has passed over 20%, the performance of Sb 2 (S,Se) 3 solar cells is still far behind. Up to now, it is still critical to enhance efficiency as well as achieve fundamental understanding.…”
mentioning
confidence: 99%